Analisis Kebijakan Peruntukan Tata Ruang dan Pembebasan Tanah (Studi Kasus Konflik Pembangunan Pabrik Gula PT. GMM Di Desa Tinapan, Kecamatan Todanan, Kabupaten Blora) - Wibiseno Udiaji; Turtiantoro .; Edi Santoso (Journal of Politic and Government Studies, 2014)
Sugar development PT. GMM policy in the Tinapan Village, District Todanan, Blora is one manifestation of a policy of self-sufficiency that has been established by the Provincial Government of Central Java in 2013. Construction of sugar factory PT. GMM state located on the ground used by scouts Kwarcab Blora.2Some parties such as NGO’s Tidal protest against obscurity status of land used for the construction of a sugar factory.In this study, researchers used a qualitative method that will generate descriptive data. To obtain research purposes appropriate data sources, researchers used purposive sampling techniques to conduct interviews with BPMPP Blora, Bappeda Blora, BLH Blora, Disperindakop Blora, Scout Kwarcab Blora, Parliament Blora, Tidal NGOs, village head Tinapan, former village head Tinapan.The results showed spatial policy of development sugar factory PT. GMM by occupying government land Blora Bentolo mention that there are rules that the District Todanan a karst area of land and irrigation lines that must be traversed to get protection. Map conflicts sugar plant of PT. GMM horizontally involve NGO’s with Scout Kwarcab Tidal Blora and PT. GMM. Vertically ebb and involve NGO’s with government stakeholders such as the Office of Land and the Environment Agency Blora.Researchers recommend, in determining the development policy of the sugar factory of PT. GMM on the conformity with the Spatial area should be studied more in depth back so do not overlook the use of space in which there are land use and water is the most important issue.